Epigenetics in type 1 diabetes: TNFa gene promoter methylation status in Chilean patients with type 1 diabetes mellitus. Issue 11 (28th November 2016) - Arroyo-Jousse, Viviana; Garcia-Diaz, Diego F.; Codner, Ethel; Pérez-Bravo, Francisco
Abstract: TNF- α is a pro-inflammatory cytokine that is involved in type 1 diabetes (T1D) pathogenesis. The TNFa gene is subject of epigenetic regulation in which folate and homocysteine are important molecules because they participate in the methionine cycle where the most important methyl group donor ( S -adenosylmethionine) is formed. We investigated whether TNFa gene promoter methylation status in T1D patients was related to blood folate, homocysteine and TNF- α in a transversal case–control study. We studied T1D patients ( n 25, mean=13·7 years) and healthy control subjects ( n 25, mean=31·1 years), without T1D and/or other autoimmune diseases or direct family history of these diseases. A blood sample was obtained for determination of serum folate, plasma homocysteine and TNF- α concentrations. Whole blood was used for the extraction of DNA to determine the percentage of methylation by real-time PCR and melting-curve analysis. Results are expressed as means and standard deviations for parametric variables and as median (interquartile range) for non-parametric variables. T1D patients showed a higher TNFa gene promoter methylation (39·2 (sd 19·5) %) when compared with control subjects (25·4 (sd 13·7) %) ( P =0·008). TNFa gene promoter methylation was positively associated only with homocysteine levels in T1D patients ( r 0·55, P =0·007), but not in control subjects ( r −0·122, P =0·872). To our knowledge, this is the first work that reports the methylation status of the TNFa gene promoter and its relationship with homocysteine metabolism in Chilean T1D patients without disease complications.